The Digital Archiving of Endangered Language Oral Traditions: Kaipuleohone at the University of Hawai‘i and C’ek’aedi Hwnax in Alaska - Andrea L., Berez (Center for Studies in Oral Tradition, 2018)
This essay compares and contrasts two small-scale digital endangered language archives with regard to their relevance for oral tradition research. The first is a university-based archive curated at the University of Hawai‘i, which is designed to house endangered language materials arising from the fieldwork of university researchers. The second is an indigenously-administered archive in rural Alaska that serves the language maintenance needs of the Ahtna Athabaskan Alaska Native community.